KEDUDUKAN HUKUM SURAT KEPUTUSAN KEPEGAWAIAN PEGAWAI NEGERI SIPIL SEBAGAI JAMINAN KREDIT - Turnip, Anju Chornelus; Talubun, Richardus F. (LPPM Universitas Bina Insan, 2022)
Bank financial institutions have a role in developing the economic system. Banks have a role as distributors and collect funds from the public. The collection process involves receiving funds from the public in the form of savings. Meanwhile, in the process of distributing funds, banks provide credit to the public in the form of loans or credits. In providing credit, banks generally provide additional charges in the form of collateral. Guarantees are intended to provide certainty regarding the debtor's ability to pay off debts, which are also intended to avoid the risk of bad credit. In the case of bad credit, collateral is used as a medium or object in resolving the problem. So in this case the collateral object must have value and can be transferred. Pay attention to this problem. The existence of a Civil Servant Decree as a collateral object in a credit agreement has various problems. This is based on the legal power of the Civil Servant Decree as an object for resolving credit disputes. A Civil Servant Decree is a letter containing the decision to appoint a Civil Servant along with other regulations relating to salary, rank, term of service and other rules relating to ethics